KONSELING KELUARGA SENSITIF GENDER DALAM MENGATASI PERCERAIAN - Uswatun Hasanah (Jurnal Studi Gender dan Anak, 2019)
Marriage counseling is counseling held as an educational method, a method of reducing emotional tension, a method of helping married partners to solve problems and how to determine a better problem solving pattern. The problem of family relations needs to be dealt with properly and effectively, through therapeutic models and techniques. One therapy effort that can be done with marriage counseling. Divorcement is a very unwanted event for every couple and family. Divorcement that occurred caused a lot of unpleasant things and pain that was felt by all parties, including both partners, children, and the two extended families of the couple. There are many factors that require couples to separate or divorce. One reason for divorced couples is a communication problem. The writing of this paper uses a social psychology approach with qualitative data analysis techniques.